Surgical Approaches for Tibial Plateau Fractures - Kandemir, Utku; Maclean, Jeffrey (The Journal of Knee Surgery, 2014)
Tibial plateau fractures are common yet complex injuries, and include a wide variety of fracture patterns. They are also potentially associated with significant soft tissue injury. Thus, the surgeon preparing to operate on one of these fractures must choose from a variety of surgical approaches that have been described. The choice of approach is dictated principally by the fracture pattern, with consideration of the soft tissue envelope, patient factors, and associated injuries. Occasionally, associated intra-articular injuries may also need to be addressed. Commonly used approaches to the proximal tibia, which together allow for the treatment of any proximal tibia fracture, will be described in this article.
Keywords: tibial plateau fracture; surgical approach; fibular osteotomy